Catalytic conversion of microcrystalline cellulose to nanocellulose using iron oxide catalysts - Suppiah, Durga Devi; Johan, Mohd Rafie (NISCAIR, 2019)
Catalytic conversion of microcrystalline cellulose (MCC) to nanocellulose involves a one-pot homogeneous reaction carried out by the cleavage of β-1,4-glycosidic bonds within the cellulose network. Through this work, the synergistic combination of ultrasonication and catalyst has been proved to be effective in the controlled depolymerisation process of cellulose. Iron oxide being a Lewis acid catalyst has been used to abstract the single electron from the electron-rich C-O bond in cellulose. The iron oxide, maghemite (γ-Fe2O3) shows the highest activity as determined by the increase of crystallinity index (CrI%) from 80.62% to 85.63%. The other phases of iron oxide also showed catalytic activity with hematite (Fe2O3) at 84.05% and magnetite (Fe3O4) at 83.39%. Morphology and particle size analysis clearly show that the nanocellulose have been obtained in the range 78 nm to 220 nm due to the structural dimension measurement of both thickness (diameter) & length. Spectroscopy analysis via Fourier transform infrared and Raman shows no changes to the functional group, hence the chemical composition and integrity of cellulose remains intact. Nanocellulose suspension obtained using maghemite exhibited the highest colloidal stability and surface tension making it more suitable for application.